Comparative Appraisal of Biomass Production, Remediation, and Bioenergy Generation Potential of Microalgae in Dairy Wastewater - Brar, Amandeep; Kumar, Manish; Pareek, Nidhi (Frontiers in Microbiology, 2019)
The present study is a trail to integrate the phycoremediation and bioenergy production from microalgal species cultivated in the dairy wastewater. Higher biomass productivities for Chlorella pyrenoidosa (24.44±8.02 mg L-1d-1), Anabaena ambigua (23.64±5.69 mg L-1d-1) and Scenedesmus abundans (18.72±2.06 mg L-1d-1) were recorded in 3:1 dairy wastewater (DWW) over the control. The microalgal species have effectively reduced the BOD by 56%, COD by 77%, nitrate by 88% and phosphate by 85% following 25 days of the cultivation in the 3:1 DWW. The total lipid content was 10.36%, 13.13% and 16.93% of dry matter of biomass in C. pyrenoidosa, A. ambigua and S. abundans, respectively following 25 days of cultivation in the 3:1 ratio of DWW. The biochemical characterization revealed that the protein content was 21.8 % in C. pyrenoidosa, 17.73 % in A. ambigua and 34.06 % in S. abundans. The estimation of theoretical methane potential suggested that the microalgal species have the desirable possibility of biogas generation. The results have marked the achievability of an integrated process for the remediation and bioenergy production by the employment of microalgal species.